BULK-SYNCHRONOUS PARALLEL ALGORITHMS FOR QR AND QZ MATRIX FACTORISATION - CALINESCU, RADU; EVANS, DAVID J. (Parallel algorithms and applications, 1997)
This paper presents bulk-synchronous parallel (BSP) algorithms for linear system solving through QR and QZ factorisation. The two new algorithms are analysed in terms of the BSP cost model, and portable implementations of the QR and QZ decomposition methods are devised using the Oxford BSP Library. The experimental results obtained on a shared-memory multiprocessor accurately match the theoretical predictions, permitting a thorough comparison of the two algorithms.